A family affair: Evidence of chain migration during the mass emigration from the county of Halland in Sweden to the United States in the 1890s. (2nd January 2020) - Eurenius, Anna-Maria
Abstract : This paper examines the influence of individual and household factors on an individual's propensity to emigrate from Halland, a region in south-west Sweden, to the United States during the era of mass migration in the late nineteenth century. The study has a case–control design, using individual-level longitudinal data for a group of emigrants (cases) and a group of non-emigrants (controls). Results indicate the importance of a family's emigration history; individuals whose relatives had previously moved to the United States were more likely to emigrate themselves. In addition, the results also show how this impact varied between groups and how other factors relating to the individual's life situation affected the migration decision. Thus, this paper shows how chain migration and migration networks play important roles during times of mass migration.